Performance Evaluation of DSR, AODV, and OLSR Routing Protocols in MANET - Alaa Azmi, Allahham; Mohammed, Muamer N.; Sadiq, Ali Safa (2016)
In recent years, Mobile Ad-hoc Networks (MANETs) is one of the popular research areas due to low cost to employ the network, self-organization, freedom of location, and no base stations. However, broadcast and data aggregation are crucial operations in MANETs. Design of MANET networks with high efficiency is an important task because the nodes in MANET have limited resources for communication such as bandwidth, buffer space, and battery power. Moreover, because of the high mobility of nodes, nodes may change their positions rapidly and these will not only change the network topology, but also make it impossible to keep a durable and regular data routing between two nodes, that can cause link failure. There are many routing protocols that are designed to work in the ad hoc networks, but many challenges continue to push for further improvements in its performance to increase the effectiveness of the networks.In this paper, the performance evaluation of the three routing protocols (DSR, AODV, and OLSR) that are widely used are presented, also compare is the performance of the three networks in different scenarios in terms of the network size and node speed. The results shows a substantial convergence performance of these network protocols in a small-sized networks, but the performance begins to varies with the increasing size of the network.